Paternity leave’s effect on male suicide and violence in Sweden - Trüschel,Sam (2025)
This essay gives insight into fatherhoods relationships with societal issues often connected with masculinity by researching the effect of paternity leave on male suicide, domestic violence, and general violence in Sweden. Correlation analysis and linear regression was used on governmental data over Sweden’s municipalities. The results confirm implications of previous literature in that that higher proportion paternity leave correlates with lower rates of male suicide and repeated violence victimisation, thought these correlations are not particularly strong. Previous literature presents two related causal explanations for the reduction in male suicide and repeated violence, one being a redefining effect of masculinity through childcare and the other being an equalizing effect on patriarchal power structures. The one variable that did have a significant correlation was domestic violence though when controlling for men’s view on equality paternity leave was, contrary to previous research, associated with an increase in domestic violence. Although further research is needed to evaluate policy effect, the result of this study generally supports increases in number of fathers taking parental leave as a policy goal though it also show that paternity leave might have hidden harmful effects through domestic violence.
Keywords: Parental leave; Masculinity; Fatherhood; Suicide; Domestic violence